(untitled) (Applied Sciences in Dentistry, 2021)
Objective: Compare the effects of different pre-cementing cleaning protocols on adhesive bond strength (MPa) in indirect composite resin restorations contaminated with saliva. Materials and Methods: 110 tests bodies of indirect composite resin, divided into 2 groups: with no contamination (NC); with contamination (WC); distributed in 22 subgroups (n = 5) according to the Ultrasound (U) variables; Cleaning Paste (CP); Ethanol 96 ° (E), Application times: 5-20-30-180s. Five cylinders (1mm high x 0.7 Ø) of cement (Variolink Esthetic LC) per sample made on treated and light-cured surfaces (20s). After 24hrs / 37ºC + distilled water, they were subjected to the RUA test (0.5 mm / min) until fracture point in a universal test machine. Analyzed with one-way ANOVA and post hoc Tukey test (α = 0.05). Results: Contaminated CP30’’ was the protocol with the highest binding resistance (14.57 ± 1.01) (p <0.05). Conclusion: The gold standard technique - corresponding to ultrasonic washing - is unrecommended for cleaning indirect composite resin restoration, seen as there are other more effective protocols to eliminate surface contaminants. Cleaning paste and Ethanol in times of 20’’ or 30’’ are suggested.